Teacher Creativity in Making Learning Media in MIN 3 Medan City (Literasi Nusantara, 2023)
This research is motivated by the importance of teacher creativity in making learning media. This can be seen from the existence of learning media made by teachers themselves before starting the learning process and then applying it in the learning process. From this search, researchers are interested in conducting research on teacher creativity in making learning media at MIN 3 Medan City. This study aims to reveal how the creativity of teachers in making learning media at MIN 3 Medan City. Starting from the selection of types of learning media, making learning media and applying learning media. This research was conducted using qualitative research methods with a naturalistic approach. Data collection through observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion drawing. The results of this study show that the creativity of teachers in making learning media is good. Because teachers use visual and audio-visual media types, teachers make learning media sourced from their own creativity to produce a learning media and also make good use of the internet to add media making sources. In terms of the application of learning media, teachers refer to the lesson plans that have been made and involve children in the learning process by direct practice using the media.